Feed Digestibility in Catfish (Pangasius sp.) with the Addition of Different Dose of Prebiotics - Muhlisoh Muhlisoh (Jurnal Perikanan dan Kelautan, 2015)
Catfish (Pangasius sp.) is one of the freshwater fish which have high economic value. The optimal level of protein to support the growth of catfish ranged from 25 - 35%. The aims of this research was to the know effect of the addition of prebiotics in the improvement of feed digestibility value in catfish. The results showed that the total digestibility was 81.68 ± 2.46%, protein digestibility was 90.71 ± 0.77%, fat digestibility was   87.05 ± 1.07%, crude fiber digestibility was 49.79 ± 8.51% and energy digestibility was 87.25 ± 3.40%. The best results of feed was found in the addition of 3% prebiotic.